The Counselor’s Role in Mitigating the Negative Impact of Social Media Oversharing on Adolescent Mental Health - Febriella Fauziah; Azzahra Fitri Himelyani; Arini Azmi; Tiara Septia Agus; Amanda Natasya Fitri (Program Studi Bimbingan Konseling, Fakultas Tarbiyah dan Ilmu Keguruan UIN Bukittinggi, 2025)
In the digital age, adolescent are increasingly vulnerable to the phenomenon of oversharing - the tendency to over-share personal information via social media. This practice, while often motivated by the need for social connection and validation, has been shown to negatively impact students' mental health. This article aims to comprehensively explore the role of counselors in mitigating the negative impact of social media oversharing on adolescent. The research was conducted through a literature review and analysis of current literature on the relationship between oversharing, mental health, and the interventions that counselors can provide. The results of the analysis show that oversharing can trigger anxiety, sleep disorders, decreased self-esteem, and increase the risk of cyberbullying. Counselors have a strategic role in providing digital literacy education, cognitive-behavioral therapy, emotion regulation training, and continued psychological support. With the right strategy, counselors can become agents of change in creating a culture of healthy and ethical information sharing among students. This study concludes that counsellors need to have adequated knowledge and skills to address the issue of social media oversharing and its impact on adolescent mental health.